Inventory of Pathogenic Fungi by Red Chili Seeds (Capsicum annuum L.) from Deli Serdang Regency, North Sumatera - Sukapiring, Dewi N; Novianty, Lily; Harahap, Siti Nurlani (Universitas Labuhanbatu, 2023)
Red chilies known as Capsicum annuum L., hold significant importance as horticulture crops in Indonesia. The production of red chilies begins with the planting of seeds, making seed health a crucial factor in the process. Seeds contaminated with pathogens can serve as a reservoir for the transmission of diseases in the field, leading to the demise of seedlings and hindering their growth into fully mature plants, ultimately resulting in crop failure. This study used the blotter test technique to ascertain the morphology of a seed-borne pathogenic fungus. The research findings indicated that the blotter test technique detected four isolates of seed-borne pathogenic fungus, specifically TMIA with an infection rate of 0.5%, TMIB with an infection rate of 0.5%, TMIC with an infection rate of 2.5%, and TMIE with an infection rate of 3%. A single isolate of a seed-borne pathogenic fungus, named SRIA, was obtained from Sidodadi Ramunia village. The infection rate of this fungus was determined to be 0.5%. The chili seeds recovered were found to carry pathogenic fungal isolates belonging to Aspergillus sp., Penicillium sp., Verticillium sp., and Curvularia sp. based on morphological identification